A Window on Econometrics. - Hendry, D; Doornik, J (1995)
This paper illustrates how econometricians practice their subject using primarily graphical tools. It is based on software which exploits the Windows operating system to show data, results, reports, and graphics simultaneously on screen and seeks to capture the interactions which were used in the associated lecture to highlight the learning process involved in econometric modelling. The substantive application is a model of the UK inflation process over the past century, which finds an important role for excess demand for goods and services, with additional pressures from excess money, national debt, and deviations from purchasing power parity.